2017
DOI: 10.1093/eurpub/ckx112
|View full text |Cite
|
Sign up to set email alerts
|

Perception and use of Pap smear screening among rural and urban women in Romania

Abstract: Because the uptake and the success of cervical cancer screening are determined by women's knowledge and awareness of Pap smear, it is critical to improve these perceptions in the near future especially in rural area characterized by a low socio-economic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
9
0
2
Order By: Relevance
“…Low coverage is directly affected by the targeted population, and accordingly, there have been numerous studies in various countries evaluating the awareness, perception, and knowledge of the population in regard to HPV, cervical cancer screening programs and vaccination programs [141,172,205,209,219,247,251,255,258,283,320,321]. These studies also highlight the importance of health care providers, general practitioners and gynecologists, both in opportunistic screening and in organized programs [128,207,327].…”
Section: The Current Landscape Of Cervical Cancer Screening In Thementioning
confidence: 99%
“…Low coverage is directly affected by the targeted population, and accordingly, there have been numerous studies in various countries evaluating the awareness, perception, and knowledge of the population in regard to HPV, cervical cancer screening programs and vaccination programs [141,172,205,209,219,247,251,255,258,283,320,321]. These studies also highlight the importance of health care providers, general practitioners and gynecologists, both in opportunistic screening and in organized programs [128,207,327].…”
Section: The Current Landscape Of Cervical Cancer Screening In Thementioning
confidence: 99%
“…Women do not identify risk factors for cervical cancer, less than half of the women studied have ever heard about HPV, and many less perceive the link between cervical cancer and HPV (Robison et al., 2014). Some studies have suggested that women with higher educational levels, those older and married and the ones who have had an abnormal Pap test result usually know more about cervical cancer and its prevention (Anwar et al., 2018; Grigore et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors of the qualitative study argued that the main barrier was the screening system itself, which they said was not tailored to the targeted audience. Another study on the national screening program found significant differences between women in rural and urban areas in terms of knowledge and acceptance of the Pap smear (Grigore et al 2017). The authors noted that 97.5 percent of women in urban areas and 92 per-cent of women in rural areas had heard about the test.…”
Section: Risky Behavior Appears To Be a Contributing Factor Inmentioning
confidence: 99%